Gendering Pacification: Policing Women at Anti-fracking Protests. Issue 2 (July 2019) - Monk, Helen; Gilmore, Joanna; Jackson, William
This article seeks to consider the policing of anti-fracking protests at Barton Moss, Salford, from November 2013 to April 2014. We argue that women at Barton Moss were considered by the police to be transgressing the socio-geographical boundaries that establish the dominant cultural and social order, and were thus responded to as disruptive and disorderly subjects. The article draws upon recent work on pacification, which views police power as having both destructive and productive dimensions, to consider the impact of police violence on women involved in protest. We seek to explore the ways in which this violence impacts not only on those involved in protest but also those on the peripheries. The article suggests that the threat and use of sexual violence by police towards women aims to enforce compliance within the protest movement and to send a message, specifically to those on the fringes of the movement, that protest is illegitimate and inherently dangerous. As such, sexual violence forms part of the social production and construction of gender and is instrumental in the making and remaking of subjectivities. The case study suggests that police brutality towards women at Barton Moss, therefore, operated as a disciplinary function to regulate acceptable forms of protest and acceptable forms of femininity.